2022
DOI: 10.3390/md20070428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Light Intensity on the Polar Lipidome of Endophytic Brown Algae Streblonema corymbiferum and Streblonema sp. In Vitro

Abstract: The effect of temperature and light intensity on the polar lipidome of endophytic brown algae Streblonema corymbiferum and Streblonema sp. in vitro was investigated. More than 460 molecular species have been identified in four glycoglycerolipids classes, five phosphoglycerolipids classes and one betaine lipid class. The lipids glucuronosyldiacylglycerol and diacylglyceryl-N,N,N-trimethyl-homoserine were found in the algae of the order Ectocarpales for the first time. A decrease in cultivation temperature led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…An increase in the content of highly unsaturated MGDG molecular species may be associated with a reduced level of illumination due to the short duration of daylight hours in winter. A similar adaptive response in brown algae of the genus Streblonema cultivated at low light intensity was described [ 36 ].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…An increase in the content of highly unsaturated MGDG molecular species may be associated with a reduced level of illumination due to the short duration of daylight hours in winter. A similar adaptive response in brown algae of the genus Streblonema cultivated at low light intensity was described [ 36 ].…”
Section: Resultsmentioning
confidence: 60%
“…Plastid-derived forms of extraplastidic lipids have been identified, suggesting that DAG may be transported from plastids to synthesize these lipids. Based on the data from the literature [ 46 , 47 , 48 ], as well as data obtained as a result of the analysis of the FA positional distribution in the molecules of different lipid classes of four species of brown algae ( Table S3 , [ 36 ]) from two orders (Laminariales, Ectocarpales), a scheme of lipid molecular species biosynthesis pathways was constructed ( Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…347 One study has examined the effects of temperature and light on lipid production in two different Streblonema algae, with the concentrations of various polar glycerol-derived metabolites varying significantly following exposure to low or high light intensities. 348 The structure of a tetraprenylated chromane has been revised to 883 following in-depth J-based configurational analysis coupled with comparison of experimental and calculated chiro-optical properties. 349 A seasonal study of the volatilome of both fresh and dried Croatian Dictyota dichotoma has indicated that the main volatile components are short chain lipids or are diterpenoid in origin, with distinct variation throughout the months of the study facilitating statistical differentiation of the sample treatments.…”
Section: Brown Algaementioning
confidence: 99%
“…For example, in Tetraselmis subcordiformis , N. oculata and Parachlorella kessleri , the response temperature of lipid accumulation of each microalga is different [ 153 , 154 ]. Besides, a decrease in the culture temperature leads to the shift of desaturases activity and an increase in the unsaturation level in FAs, which ensure the cell membrane fluidity under temperature stress conditions [ 155 158 ]. These findings suggest that the lipid content and FAs composition of microalgae can be influenced to a certain extent by temperature control.…”
Section: Selection and Cultivation Of Microalgae Strainsmentioning
confidence: 99%